2021
DOI: 10.3390/ijms22157979
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics Insights of Alpha-Lipoic Acid against Cardiovascular Diseases during COVID-19 Infection

Abstract: Coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, in late December 2019. Since then, COVID-19 has spread rapidly worldwide and was declared a global pandemic on 20 March 2020. Cardiovascular complications are rapidly emerging as a major peril in COVID-19 in addition to respiratory disease. The mechanisms underlying the excessive effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on patients with cardiovascular comorbidities remain only partly understood. SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 127 publications
0
17
0
Order By: Relevance
“…This change in glucose handling markedly alters the metabolism of the mitochondria, which is critical to limiting cellular dysfunction, resisting disease, and preventing organismal death. Indeed, there are numerous maladies that are specifically classified as mitochondria-related diseases [121][122][123][124][125] with this category, including viral infections, such as SARS-CoV-2 [126][127][128][129].…”
Section: Discussionmentioning
confidence: 99%
“…This change in glucose handling markedly alters the metabolism of the mitochondria, which is critical to limiting cellular dysfunction, resisting disease, and preventing organismal death. Indeed, there are numerous maladies that are specifically classified as mitochondria-related diseases [121][122][123][124][125] with this category, including viral infections, such as SARS-CoV-2 [126][127][128][129].…”
Section: Discussionmentioning
confidence: 99%
“…It also plays an important role in a variety of other biological functions (redox signaling, regulation of protein functions, amino acid transportation, DNA synthesis, proliferation, apoptosis, detoxification, inflammation, and immune function) [1,2]. GSH deficiency is associated with various diseases, such as cardiovascular, neurodegenerative, and pulmonary diseases; cancer; HIV; and diabetes [3][4][5][6][7]. Recent studies have shown that GSH may be a marker of severity and a promising target for co-therapy of novel coronavirus infection (coronavirus disease 2019) [8,9].…”
mentioning
confidence: 99%
“…An increasing body of literature data indicates that LA may boost also human host defense against SARS-CoV-2 [ 127 , 128 ]. It is commonly known that the LA/DHLA system inhibits NF k B signaling with a decrease in pro-inflammatory cytokine secretion.…”
Section: Lipoic Acid (La) and Covid-19mentioning
confidence: 99%